Correlation between HEART risk score and changes of angiographic findings in patients with acute coronary syndromes - Yi, Chan Xin (2017)
Introduction: A common symptom that patients present in the Emergency & Trauma Department (ED) is chest pain which can be due to a cardiac or non-cardiac cause. It is difficult for clinicians to differentiate a life threatening chest pain from other possible causes. The HEART score is a simple and convenient tool to risk stratify patients with chest pain. This diagnostic process is to classify both low and high risk patients presented to the ED with chest pain. Meanwhile, an angiography is an invasive procedure to determine the severity of coronary disease, in which a stent can be inserted as a treatment method. This study aims to determine the correlation between HEART score and angiography findings in acute coronary syndrome patients. Objective: General objective of this study was to determine HEART SCORE level in patient with chest pain who underwent angiogram in Hospital Universiti Sains Malaysia (HUSM) and Hospital Raja Permaisuri Bainun (HRPB). The specific objective in this study were to determine 1. Correlation between HEART score and angiogram finding in patient who presented to HUSM and Hospital Raja Permaisuri Bainun with chest pain. 2. Sensitivity and specificity of HEART score in determine severity of coronary artery disease. Methods: A retrospective study was conducted in HUSM and HRPB. Medical records for year 2013 and 2014 from both hospitals were traced and reviewed. A total of 126 medical records were used in this study, where 66 were from HUSM and 60 from HRPB. The list of patients from both hospitals of those who had undergone an angiography was acquired. Patients’ HEART scores were calculated on admission and the angiography results of the same patients were recorded. The HEART score is composed of 5 components: history,electrocardiogram (ECG), age, risk factors and troponin. For each component 0, 1 or 2 points is given. Patient were then categorized into low risk group where total HEART score of the patient range from 0-3 and high risk group where patient score 4 and above. Meanwhile, the angiography result provides information of heart (coronary) arteries and was determined by the percentage of stenosis (narrowed area inside blood vessels). Results: Out of 126 patients, 96 of them were male (76.2%) and 30 were female (23.8%). The mean age was 55.8 (SD 10.67) years. The mean HEART score in this study was 5.43 (SD 1.84) points out of total score of 10 points. Eighteen out of 126 patients were categorised as low risk patients. An angiography results of 81 patients showed stenosis more than 70% and 45 patients showed stenosis less than 70%. The result of analysis showed that every increase of 1 score in the HEART score calculation, the odd of the patient to has stenosis which more than 70% increase 2.03 times [OR=2.03 (1.44; 2.85)]. There was a weak positive correlation between the total HEART score and stenosis in all the 3 major vessels in the heart left anterior descending coronary artery (LAD) (r=0.385, p= 0.001), left circumflex artery (LCX) (r=0.387, p=0.001 and right coronary artery (RCA) (r= 0.477, p=0.001) . The sensitivity of HEART score to predict stenosis more than 70% is 96.3% while the specificity is only 33.3%. Area under the ROC curve r=0.648 [CI95% 0.542-0.755; p <0.006]. Conclusion: HEART score can be used in clinical to predict the severity of coronary artery disease. HEART score as well as a very sensitive tool to predict patient who has stenosis which is 70% or more.